The Assessment of Water Quality Parameters Due to High and Low Flow for Batu Pahat River, Johor - Hazritauding, Muhammad Amiriqmal (Recent Trends in Civil Engineering and Built Environment, 2021)
Development and urbanization have increased pollutants entering the river in recent years. A rise in the number of pollutants entering the river body threatens the river, which serves as an essential water resource. These pollutions originate in a variety of locations, including industry, agriculture, and livestock. The Batu Pahat River is classified as a Class II river, meaning it's slightly polluted. The deterioration of water quality in the Batu Pahat River prompted this investigation to assess the river's water quality status under high and low flow conditions. There are 11 checkpoints along Batu Pahat River. River flow discharge can affect water quality. During low flow, less water is available to dilute pollutions, resulting in a higher concentration of pollution. Therefore, a correlation analysis between water quality index and flow rate is necessary. Water quality sampling was performed at a particular river-side checkpoint. Each checkpoint has different pollutant and land-use characteristics observed. The DOE Malaysia Standard was used to calculate the water quality index. Based on the water quality result, water quality status for Batu Pahat River can be classified as Class III. During low and high flow conditions, most checkpoints changed the Water Quality Index. At low tide and high tide, the discharge was calculated to determine the water released. The Pearson Correlation Coefficient was thus used to determine the correlations between the water quality index and flow rate. There is a positive connection between low- and high-flow water quality with 0.4007 and 0.327 respectively. Most standards considered the correlation analysis a weak correlation. This indicates that flow discharge only had some impact on the water quality index.